Gastroprotective Effect of Chitosan- Based Formulation with Chromolaena odorata L. and Peperomia pellucida L. Extracts in Ethanol-Induced Gastric Injury in Rats - Pertiwi, Reza; Prima Yudha, Sal; Notriawan, Doni; Giri Samudra, Agung; Hanuun, Aanisah; Prameswari, Florencaya Prameswari; Bekti Widiansyah, Alif; Saputra, Hendri (Universitas Ahmad Dahlan, 2025)
Gastroprotection refers to the effect of compounds that protect the gastric mucosa. Peperomia pellucida L. and Chromolaena odorata L. have demonstrated gastroprotective activities. Chromolaena odorata L., in particular, shows inhibition of gastric mucosal damage due to the presence of secondary metabolites such as flavonoids, phenolics, and tannins. Chitosan is a drug carrier that enhances drug bioavailability and allows pharmacological effects to be achieved at lower doses. This study aims to evaluate the gastroprotective activity of chitosan-based formulations containing Peperomia pellucida L. and Chromolaena odorata L. leaf extracts in rats. The contribution of this research lies in demonstrating the synergistic potential of medicinal plant extracts with chitosan as a delivery system, thereby providing a safer, more effective, and innovative therapeutic strategy for gastric ulcer management. Chitosan formulations containing Peperomia pellucida L. and Chromolaena odorata L. extracts were prepared and tested on male rats. The rats were divided into seven groups: Group I (normal control), Group II (negative control), Group III (positive control, treated with sucralfate), Groups IV and V (treated with chitosan-Chromolaena odorata formulations at doses of 100 and 200 mg/kg BW), and Groups VI and VII (treated with chitosan-Peperomia pellucida formulations at doses of 100 and 200 mg/kg BW). Treatments were administered orally for 14 days. On day 14, one hour after the final treatment, all groups except the normal group received oral absolute ethanol at a dose of 5 mL/kg BW to induce gastric injury. Gastric ulcer index, protection ratio, and histopathological changes were evaluated. The ulcer index values for the negative control, positive control, and treatment groups with doses of 100, 200, and 400 mg/kg BW were 4.89, 0.89, 0.33, 0.11, 1.00, and 0.78, respectively. The chitosan-based formulations containing Chromolaena odorata L. and Peperomia pellucida L. extracts demonstrated significant gastroprotective effects in ethanol-induced gastric injury in rats.